An unusual ectomycorrhiza-like structure from shorea leprosula (dipterocarpaceae). - Su See, Lee (1991)
An unusual mycorrhiza-like structure is described. It has no harting net but possesses a well developed and unusual haustoria-like structures projecting into the cells of the root cortex. It is not known whether the relationship is a symbiotic or parasitic one.